2015
DOI: 10.4028/www.scientific.net/amm.754-755.400
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chloride Environment on Compressive Strength of Geopolymer Concrete with Fly Ash Using Taguchi Approach

Abstract: This study is conducted to determine the effect of four variables on compressive strength of geopolymer concretes. These four variables are binder/aggregate, Alkalinene/fly ash, effect of superplasticizer (SP) addition and curing system. The compressive strength is important mechanical properties for construction material. Taguchi experimental design method is used to compile the concrete composition of geopolymer to achieve the maximum compressive strength. Specimens concrete used is a cylinder with 100 mm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…These compounds are the source of strength in the concrete with the hydration process. On the other hand, geopolymer concrete is a green technology which is currently being developed [5][6][7][8][9][10][11] for the material structure [12]. The main factor that becomes the appeal of geopolymer concrete is the polymerization process, the process of transforming material alumino-silicate oxide and alkaline activator into polysilicate product that has high mechanical strength without using cement.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are the source of strength in the concrete with the hydration process. On the other hand, geopolymer concrete is a green technology which is currently being developed [5][6][7][8][9][10][11] for the material structure [12]. The main factor that becomes the appeal of geopolymer concrete is the polymerization process, the process of transforming material alumino-silicate oxide and alkaline activator into polysilicate product that has high mechanical strength without using cement.…”
Section: Introductionmentioning
confidence: 99%
“…Ekaputri [14] calculated the safety factor to obtain the structure performance in sea water and it was found that the protection of structure has been declined year by year. Bayuaji, et al [8] found that geopolymer concrete cured in sea water provides higher compressive strength than the other curing system using fresh water and room temperature. Giasuddin [16] explained that there is abundance of Na + in the surrounding medium in salt water curing.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Denser concrete will lead against destructive agents to penetrate and flow through the pores [7]. However, the chloride environment sometimes can increase the compressive strength of the geopolymer concrete [8]. According to some previous research, fly ash-based geopolymer concrete has better durability than Portland-based concrete in aggressive environment such as sulphate, acid, and fire [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of local materials to support the infrastructure needs of the sea needed to be examined to indicate that local material in Indonesia had the potential to be used as building materials and structural materials, as conducted by the previous research [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%